1995
DOI: 10.1111/j.1439-0507.1995.tb00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐antibiotic effect and post‐expositional polyene antagonism of azole antifungal agents in Candida albicans: dependence on substance lipophilia

Abstract: The lipophilic azoles itraconazole (ICZ), ketoconazole (KCZ) and miconazole (MCZ) have two things in common regarding their effect on Candida albicans. First, these azoles cause a growth inhibition that persists for at least 24 h after exposure (post-antibiotic effect), although this is only occasionally observed for ICZ. Secondly, these substances cause a decrease in the fungicidal activity of amphotericin B (AMB, 1 mg l-1) upon subsequent exposure to this drug. In contrast, fluconazole (FCZ) exhibits neither… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…(ii) Adsorption to the cell surface by one agent inhibits binding of another antifungal agent to its target site of activity. This mechanism is proposed for lipophilic azoles (such as itraconazole and ketoconazole) which may adsorb to the fungal cell surface and inhibit binding of amphotericin B to fungal cell membrane sterols (183,185). (iii) Modification of a target upon exposure to an antifungal agent occurs that renders the pathogen less susceptible to the effects of other antifungals.…”
Section: Mechanisms Of Interactions For the Antifungal Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) Adsorption to the cell surface by one agent inhibits binding of another antifungal agent to its target site of activity. This mechanism is proposed for lipophilic azoles (such as itraconazole and ketoconazole) which may adsorb to the fungal cell surface and inhibit binding of amphotericin B to fungal cell membrane sterols (183,185). (iii) Modification of a target upon exposure to an antifungal agent occurs that renders the pathogen less susceptible to the effects of other antifungals.…”
Section: Mechanisms Of Interactions For the Antifungal Agentsmentioning
confidence: 99%
“…Antagonism among antifungal agents might occur in one of several ways. (i) Direct antifungal action at the same site results in decreased ability of other agents to exert their competitive effects on that site or at an altered target, as proposed for the azoles and amphotericin B (31,49,182,183,185,186,203). Azoles block the synthesis of ergosterol in the fungal cell membrane and may thus render amphotericin B inactive, since this agent exerts its activity by binding to ergosterol in the cell membrane.…”
Section: Mechanisms Of Interactions For the Antifungal Agentsmentioning
confidence: 99%
“…Second, AMB may not have been effectively removed by dilution when the cells were plated (29). AMB is more likely to remain bound to the cell membrane of C. albicans after plating of the cells than to diffuse into the plate medium buffer.…”
Section: Vol 47 2003 Resuscitation and Killing Of Amb-treated C Almentioning
confidence: 99%
“…AMB is more likely to remain bound to the cell membrane of C. albicans after plating of the cells than to diffuse into the plate medium buffer. For the azoles it is well established that their postantifungal effects and lipophilic nature are correlated (29), and the nonlipophilic fluconazole is the only azole that lacks a postantifungal effect (15,29).…”
Section: Vol 47 2003 Resuscitation and Killing Of Amb-treated C Almentioning
confidence: 99%
“…Moreover, several investigators have found synergistic interactions by simultaneous exposure of C. albicans to azoles and AmB (13,30). One group, on the other hand, described antagonisms with preexposures of Candida to the more lipophilic azoles, such as itraconazole, but not to fluconazole (31,32).…”
mentioning
confidence: 99%